Paramedic survival guide - DiPrima, Peter A. 4 0 16; 5 (New York : McGraw-Hill Medical, 2012)
Provides career advice for those interested in a career as a paramedic, and includes case studies, testimonials, and advice from veterans that relate the recruitment and interview process, and various career paths and options open to paramedics.
Evolution of the emergency medical services and the making of paramedicine -- Your role in the health care system as an EMS provider -- Career opportunities in EMS : now you're a paramedic -- Getting the job you want -- Taking the classroom to the streets! -- Patient safety -- Scene safety -- A day in the life of a paramedic -- One-year anniversary -- What's next for paramedics? -- State EMS agencies -- Federally sponsored EMS programs and federal agencies -- EMS associations -- Resources related to EMS -- Mental health and treatment programs.
Includes bibliographical references and index.
Adult;Adult.
Keywords: 2 -- 0; 6; Vocational guidance.;Vocational guidance. -- Emergency medical technicians.;Emergency medical technicians;Emergency Medical Technicians.;Professional Practice.;Vocational Guidance.;Emergency medical technicians.;Emergency medical technicians; 20; 2